Radial and Vertical Constraints on the Icy Origin of H2CO in the HD 163296 Protoplanetary Disk - Claudio Hernández-Vera; Viviana V. Guzmán; Elizabeth Artur de la Villarmois; Karin I. Öberg; L. Ilsedore Cleeves; Michiel R. Hogerheijde; Chunhua Qi; John Carpenter; Edith C. Fayolle (The Astrophysical Journal)
H _2 CO is a small organic molecule widely detected in protoplanetary disks. As a precursor to grain-surface formation of CH _3 OH, H _2 CO is considered an important precursor of O-bearing organic molecules that are locked in ices. Still, since gas-phase reactions can also form H _2 CO, there remains an open question on the channels by which organics form in disks, and how much the grain versus the gas pathways impact the overall organic reservoir. We present spectrally and spatially resolved Atacama Large Millimeter/submillimeter Array observations of several ortho- and para-H _2 CO transitions toward the bright protoplanetary disk around the Herbig Ae star HD 163296. We derive column density, excitation temperature, and ortho-to-para ratio (OPR) radial profiles for H _2 CO, as well as disk-averaged values of N _T ∼ 4 × 10 ^12 cm ^−2 , T _ex ∼ 20 K, and OPR ∼ 2.7, respectively. We empirically determine the vertical structure of the emission, finding vertical heights of z / r ∼ 0.1. From the profiles, we find a relatively constant OPR ∼ 2.7 with radius, but still consistent with 3.0 among the uncertainties, a secondary increase of N _T in the outer disk, and low T _ex values that decrease with disk radius. Our resulting radial, vertical, and OPR constraints suggest an increased UV penetration beyond the dust millimeter edge, consistent with an icy origin but also with cold gas-phase chemistry. This Herbig disk contrasts previous results for the T Tauri disk, TW Hya, which had a larger contribution from cold gas-phase chemistry. More observations of other sources are needed to disentangle the dominant formation pathway of H _2 CO in protoplanetary disks.